Integrative Oncology: Hope or Hype? - Rezaeizadeh, Hossein; Taheripanah, Taiebeh; Sardari, Mahdi (Reports of Radiotherapy and Oncology, 2015)
Context: According to Association of Academic Health Centers definition, integrative medicine is as a healing-oriented approach of medicine that takes account of the whole person, including all aspects of lifestyle by employing both conventional and unconventional as traditional or complementary and alternative medicine to achieve the best treatment and recovery which is the focus of the present study. Evidence Acquisition: Main oncology resources pointing to complementary and alternative medicine (CAM) modalities in cancer care, evidence-based articles, data obtained from integrative oncology clinics and government organizations associated with cancer were the materials used in this study. Results: Studies indicate the growing trend in using CAM worldwide. Generally, 38% of adults and 12% of children use CAM in United States referring national researches in 2007; however, other studies show 83 to 92 percent of cancer patient have made use of it. Most complementary modalities are noninvasive and useful in reducing symptoms and side effects of conventional treatments and improving quality of life. Some high quality scientific research has produced evidence that acupuncture, massage, music, and mind-body therapies effectively and safely reduce physical and emotional affects. Integrative oncology relates to an emerging conversation between CAM scholars, oncology care professionals, and family practitioners imagining a holistic patient-centered approach to oncology care. Conclusions: An increasing recognition in health care systems has emerged, especially in oncology of the importance of maintaining or improving patients’ quality of life all over the disease course. Cancer patients with lower quality of life are more likely to terminate therapy so this should be as an alarm to oncologist the risk for not completing therapy. Complementary methods have played a significant role in this situation for enhancing quality of life, reduced severity of symptoms and side effects, and developed general wellbeing in patients.